Synthesis and Antimicrobial Assessment of Fe3+ Inclusion Complex of p-tert-Butylcalix[4]arene Diamide Derivative. (28th March 2019) - Chandio, Anwar Ali; Ali Memon, Ayaz; Memon, Shahabuddin; Memon, Fakhar N.; Panhwar, Qadeer Khan; Durmaz, Fatih; Nizamani, Shafi Muhammad; Brohi, Nazir Ahmed
Abstract : Present study deals with the synthesis of the p - tert -butylcalix[4]arene diamide derivative as ligand (L) and its Fe 3+ complex, followed by its characterization using TLC and FT-IR, while UV-Vis and Job's plot study were performed for complex formation. Antimicrobial activity of the derivative (L) and its metal complex was carried out by the disc diffusion method against bacteria ( Escherichia coli and Staphylococcus albus ) and fungi ( R. stolonifer ). Different concentrations of the derivative (L) (6, 3, 1.5, 0.75, and 0.37  μ g/mL) and its Fe 3+ complex were prepared, and Mueller–Hinton agar was used as the medium for the growth of microorganisms. Six successive dilutions of the derivative (L) and Fe 3+ complex were used against microorganisms. Two successive dilutions (6 and 3  μ g/mL) of the derivative (L) showed antibacterial action against both Gram-positive and Gram-negative bacteria. In addition, three successive dilutions (6, 3, and 1.5  μ g/mL) of the derivative (L) showed antifungal activity. However, all of six dilutions of the Fe 3+ complex showed antimicrobial activity. Derivative (L) showed 3 and 1.5  μ g/mL minimum inhibitory concentrations (MIC) against bacteria and fungi, respectively. On the contrary, its Fe 3+ complex showed 0.37  μ g/mL value of MIC against bacteria and fungi. Hence, Fe 3+ complex of the derivative (L) was found to be a more effective antimicrobial agent against selected bacteria and fungi than the diamide derivative (L).